2021
DOI: 10.4103/2452-2473.320800
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and outcomes of geriatric tuberculosis emergencies in North India

Abstract: OBJECTIVES: Despite the acute and life-threatening repercussions that tuberculosis (TB) may have on the burgeoning older population in endemic countries like India, the spectrum of geriatric TB emergencies is not adequately understood. METHODS: We performed a prospective observational study at the emergency department of an academic hospital in north India between January 2019 and June 2020, investigating the clinical and laboratory features and outcomes of active TB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…А розвиток резистентності при використанні нестандартних схем лікування призводить до несприятливих наслідків і збільшує смертність, рівень якої серед людей похилого віку в 6 разів вищий, аніж серед молодих осіб [8]. На високий рівень смертності від ТБ серед людей похилого віку вказують й інші дослідники [1,9,10]. Для зниження смертності від ТБ із множинною лікарською стійкістю (МЛС-ТБ) у людей похилого віку, які проходять лікування, E. Kizito та співавтори [6] рекомендують приділяти увагу наданню соціальної підтримки.…”
Section: Effectiveness Of Usingunclassified
“…А розвиток резистентності при використанні нестандартних схем лікування призводить до несприятливих наслідків і збільшує смертність, рівень якої серед людей похилого віку в 6 разів вищий, аніж серед молодих осіб [8]. На високий рівень смертності від ТБ серед людей похилого віку вказують й інші дослідники [1,9,10]. Для зниження смертності від ТБ із множинною лікарською стійкістю (МЛС-ТБ) у людей похилого віку, які проходять лікування, E. Kizito та співавтори [6] рекомендують приділяти увагу наданню соціальної підтримки.…”
Section: Effectiveness Of Usingunclassified
“…11,57,58 In addition to gender differences in TB prevalence, mortality rates increased dramatically with age, being 17 times higher in children under 15 years and more than twice as common in adults 60 and older than in those between the ages of 15 and 59. 1,3,4,[10][11][12]20,28,38,41,43,46,59 Furthermore, the COVID-19 reaction-induced lockdown has resulted in poverty and economic hardship, worsening food shortages and making it more difficult to provide various TB services such as prevention, surveillance, and treatment to the vulnerable segment. 13,22,31,44,60 Children with TB had significant implications or problems during the COVID epidemic, such as requiring more mechanical breathing, being hospitalized for longer periods of time, and having poorer outcomes.…”
Section: The Burden Of Tuberculosis In Different States Of Indiamentioning
confidence: 99%
“…15,16,28,48,49,63 Additionally, several studies found that more than two-thirds of TB cases are observed in the economically productive age range (14-59 years). 1,3,4,9,10,20,31,37,38,40,41,43,46,59,73,74 The international health community, which has established multiple 5-year targets for TB elimination, has proposed a method combining improved diagnostics, medications, and vaccinations to identify and treat both latent and active TB infections in order to meet the 2050 target. 15,48,49,51 The Joint Effort for Tuberculosis Elimination Program, with TB professionals, NGOs, and private practitioners all playing crucial roles in assisting patients seeking TB treatment, has also proven successful in providing quality TB services and facilities to patients.…”
Section: Adopted Measures Challenges Faced and Tuberculosis-related P...mentioning
confidence: 99%
See 1 more Smart Citation